Dynamic hydrolase labelling as a marker for seed quality in Arabidopsis seeds - Viñegra de la Torre, N; Kaschani, F; Kaiser, M; van der Hoorn, RAL; Soppe, WJJ; Misas Villamil, JC (Portland Press, 2019)
Seed quality is affected by different constituents of the seed. In general, seed lots are considered to be of high quality when they exhibit fast and homogeneous germination. When seeds are stored, they undergo different degrees of damage that have detrimental effects on their quality. Therefore, accurate prediction of the seed quality and viability levels of a seed lot is of high importance in the seed-producing industry. Here, we describe the use of activity-based protein profiling of proteases to evaluate the quality of artificially and naturally aged seeds of Arabidopsis thaliana. Using this approach, we have identified two protease activities with opposite behaviours in aged seeds of Arabidopsis that correlate with the quality status of the seeds. We show that vacuolar processing enzymes (VPEs) become more active during the ageing process, in both artificial and natural ageing treatments. Secondly, we demonstrate that serine hydrolases are active at the beginning of our artificial ageing treatment, but their labelling decreases along with seed viability. We present a list of candidate hydrolases active during seed germination and propose that these protease activities can be used in combination with VPEs to develop novel markers of seed quality.